Emission characteristic of diamond-tip field emitter arrays fabricated by transfer mold technique - Kim, S; Ju, BK; Lee, YH; Park, BS; Baik, YJ; Lim, S; Oh, MH (AMER INST PHYSICS, 1997)
Wedge-shaped diamond-tip field emitter arrays were fabricated and characterized. The tip radius of the diamond emitter fabricated by using a silicon mold was about 300 Angstrom. The maximum current density of 800 mu A/cm(2) and the threshold voltage of 600 V were obtained from the diamond-tip held emitter array, which was a better electrical characteristic than that of a flat diamond film. The effects of vacuum pressure upon emission characteristics were investigated. The emission characteristic of the diamond-tip held emitter array was not varied over a wide range of vacuum pressure relatively to the hat diamond film. (C) 1997 American Vacuum Society.
Keywords: VACUUM MICROELECTRONICS